Process parameters control in water jet peening. (1st January 2000) - Colosimo, B.M.; Monno, M.; Semeraro, Q.
Recent researches propose the use of Water Jet technology for peening metallic components. Compared with traditional shot peening (SP), water jet peening (WJP) process presents the main advantage of a negligible influence on surface roughness and topography. Nevertheless, the transition from residual stress generation to the beginning of an erosion phenomenon is deeply influenced by an accurate selection of process parameters. Since by now parameter selection is performed by experimental trials, the paper focuses on the analysis of two main parameters the pressure and the traverse rate of the waterjet. The effect of these parameters on residual stress, roughness and erosion is investigated and empirical relationships which can explain these effects are presented.